Long-term vagal stimulation for heart failure: Eighteen month results from the NEural Cardiac TherApy foR Heart Failure (NECTAR-HF) trial. (1st October 2017) - De Ferrari, Gaetano M.; Stolen, Craig; Tuinenburg, Anton E.; Wright, D. Jay; Brugada, Josep; Butter, Christian; Klein, Helmut; Neuzil, Petr; Botman, Cornelis; Castel, Maria Angeles; D'Onofrio, Antonio; de Borst, Gert J.; et al.
Abstract: Background: The NECTAR-HF study evaluated safety and feasibility of vagal nerve stimulation (VNS) for the treatment of heart failure patients. The first six-month randomized phase of the study did not show improvement in left ventricular remodelling in response to VNS. This study reports the 18-month results and provides novel findings aiming to understand the lack of efficacy of VNS, including a new technique assessing the effects of VNS. Methods: Ninety-six patients were randomized 2:1 to active or inactive VNS for 6 months, thereafter VNS was activated for all patients. The primary safety endpoint was 18-month all-cause mortality. Results: Ninety-one patients continued in the long-term evaluation with active VNS. The on-therapy survival estimate at 18 months was 95% with a 95% one-sided lower confidence limit of 91%, (better than the predefined criterion). Left ventricular systolic volume decreased in the crossover group (VNS OFF → ON; 144 ± 37 to 139 ± 40, p < 0.05) after VNS activation; LVESD (5.02 ± 0.77 to 4.96 ± 0.82, p > 0.05) and LVEF (33.2 ± 4.9 to 33.3 ± 6.5, p > 0.05) did not change. A new technique to detect subtle heart rate changes during Holter recordings, i.e. "heat maps", revealed that VNS evoked heart rate response in only 13/106 studies (12%) at 6 and 12 months with active VNS. Conclusions: Although a favourable long-term safety profile was found, improvements in the efficacy endpoints were not seen with VNS. A new technique for detecting acute heart rate responses to VNS suggests that the recruitment of nerve fibres responsible for heart rate changes were substantially lower in NECTAR-HF than in pre-clinical models.